THE ANALYSIS OF STUDENTS’ ATTITUDE TO THE CLASSROOM ENVIRONMENT IN SMPN 2 MAYANG - Dini Atrasina Ludyas Adani; Wachju Subchan (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This study was aimed to determine students' caring behavior towards cleanliness and neatness of the messy environment, especially in their classrooms. This study used a descriptive qualitative research design. This study used a population of grade VII students at SMP Negeri 2 Mayang. The total number of class VII students in SMP Negeri 2 Mayang was 167 students. Samples taken used in this study were 124 students. The sample selection was done by a proportional random sampling method. The data collection technique used in the research was in the form of a Google form questionnaire. Based on the result, shows that 73.85% or 92 students had a good sense of environmental care because they wanted to clean the classroom when the condition was not neat, while students who were less concerned as much as 18.17% or 22 students. They still asked friends to clean the dirt in the class. For students who do not care about the environment as much as 10 students or 7.99%, because students were indifferent even though the class is dirty.